PERBEDAAN TINGKAT KECEMASAN AKSEPTOR KONTRASEPSI IUD DENGAN SUNTIK 3 BULAN DALAM MENGHADAPI EFEK SAMPING ALAT KONTRASEPSI - Dyah Permata Sari (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2016)
The hormonal contraceptive especially injection is the most widely used in Indonesia. Unlike the IUD contraception, although both have side effects that cause anxiety, but the use of IUD is still much lower than the injection. The purpose of this research was to determine differences in the level of anxiety of IUD acceptor with 3 monthly contraceptive injections in facing the side effects of contraceptives in Independent Midwife Practice Ny. T. Tampungrejo Village District of Puri Mojokerto. Research type is observational analytic with cross sectional design. The independent variable is side effects of IUD and 3 monthly injectable contraceptive. Dependent variable is levels of anxiety of IUD acceptor with 3 monthly contraceptive injections in facing the side effects of contraceptives. Population is all IUD acceptors and 3 monthly contraceptive injections which has experienced side effects as much as 91 people and obtained 74 samples by using proportionate stratified random sampling. Data were taken using questionnaire on 20-26 May 2014. After being collected, then processed and analyzed using the Mann Whitney U Test. The results showed the majority of IUD respondents have experienced severe anxiety as many as 5 respondents (62,5%) and almost half of the 3 monthly contraceptive injection respondents have experienced moderate anxiety as many as 22 respondents (33,3%). The result of Mann Whitney U Test obtained p value (0,001) < α (0,05), then H0 is rejected and H1 is accepted, there are differences in the level of anxiety of IUD acceptor with 3 monthly contraceptive injections in facing the side effects of contraceptives. IUD acceptors have severe anxiety due to the negative image of IUD and basic education. Conclusion of this research is that there are differences in the level of anxiety of IUD acceptor with 3 monthly contraceptive injections in facing the side effects of contraceptives. Midwives should increase counseling on IUD acceptor with 3 monthly contraceptive injections by providing complete information about side effects and treatment, other types of contraceptive methods if the mother wishes to change to another method of contraception, and also efforts to deal with the anxiety experienced.